A New Subclass of Harmonic Univalent Functions Associated with Dziok-Srivastava Operator. (28th November 2012) - Pathak, A. L.; Dixit, K. K.; Agarwal, R.
Abstract : The purpose of the present paper is to study a certain subclass of harmonic univalent functions associated with Dziok-Srivastava operator. We obtain coefficient conditions, distortion bounds, and extreme points for the above class of harmonic univalent functions belonging to this class and discuss a class preserving integral operator. We also show that class studied in this paper is closed under convolution and convex combination. The results obtained for the class reduced to the corresponding results for several known classes in the literature are briefly indicated.